2015
DOI: 10.1039/c5cp03561a
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced penetration of guest molecules in high-silica zeolites: the case of mordenite

Abstract: A synthetic high-silica mordenite (HS-MOR) has been compressed in both non-penetrating (silicone oil, s.o.) and penetrating [methanol : ethanol : water (16 : 3 : 1) (m.e.w.), water : ethanol (3 : 1) (w.e.), and ethylene glycol (e.gl.)] pressure transmitting media (PTM). In situ high-pressure (HP) synchrotron X-ray powder diffraction (XRPD) experiments allowed the unit cell parameters to be followed up to 1.6, 1.8, 8.4, and 6.7 GPa in s.o., w.e., m.e.w., and e.gl., respectively. Moreover, e.gl. was also used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 68 publications
(109 reference statements)
1
16
0
Order By: Relevance
“…In summary, our results have shown that neon, one of the most inert atoms, is able to form an inclusion compound with ammonium metal formates at high pressures. While other examples of either noble gas (He or Ar) or small‐molecule inclusions are known within porous network solids at high pressure, here we observe that the closed porosity of AMF at ambient conditions becomes accessible for inclusion of neon under pressure. This highlights the facile movement of the ammonium cations for allowing neon insertion throughout the metal formate structure upon compression and neon release upon decompression.…”
Section: Figurementioning
confidence: 48%
“…In summary, our results have shown that neon, one of the most inert atoms, is able to form an inclusion compound with ammonium metal formates at high pressures. While other examples of either noble gas (He or Ar) or small‐molecule inclusions are known within porous network solids at high pressure, here we observe that the closed porosity of AMF at ambient conditions becomes accessible for inclusion of neon under pressure. This highlights the facile movement of the ammonium cations for allowing neon insertion throughout the metal formate structure upon compression and neon release upon decompression.…”
Section: Figurementioning
confidence: 48%
“…They observed that the intrusion of the glycol molecules greatly enhanced the stability of the zeolite framework against pressure‐induced amorphization. Importantly, the insertion of ethylene glycol occurred already at moderate pressures – namely at 0.1 GPa, and showed features of irreversibility upon decompression . The experiment indicated that it is not necessary to use extreme pressures to introduce organic molecules in zeolites.…”
Section: Organized Materials By High‐pressure Confinementmentioning
confidence: 90%
“…The framework composition profoundly affects the uptake of the pressure medium in the zeolite channels, as demonstrated by several experiments ,,,. Whereas it was not possible to incorporate ethanol and methanol inside Na‐mordenite – which already contained six Na + and 19 H 2 O in the unit cell,, Arletti et al . reported the intrusion of these molecules into the empty pores of all silica mordenite ,…”
Section: Organized Materials By High‐pressure Confinementmentioning
confidence: 99%
“…The sample used in this work is a commercial synthetic highsilica mordenite (HS-MOR; Si/Al=200). The pristine material has been fully characterized and previously used in many studies, namely on the adsorption of pollutants from wastewaters, [78][79][80] on the intrusion of ethylene glycol and water/alcohol mixtures at high pressure (HP) [81] and in the oligomerization of phenylacetylene at HP. [55] Structural data and relevant details of the Rietveld refinements on the pristine HS-MOR here used are reported in Table 1, as well as those of the synthesized host-guest compound HS-MOR hexa, later discussed (the final observed and calculated powder patterns for HS-MOR hexa are provided in the Supporting Information, Figure 1S; atomic coordinates, occupancy factors, thermal parameters and selected bond distances (Å) are reported in Tables 1S and 2S, respectively).…”
Section: Basic Investigation Of the Host Steric Constraintsmentioning
confidence: 99%
“…An additional peak of the difference Fourier map was ascribed to a H2O molecule site in the window between the 12MR and the side pocket, corresponding to the W1 site found in the pristine sample. [81] The refinement of the occupancy factor leads to a total H2O amount of 3.5 molecules per unit cell. This is in agreement with the results of the thermal analysis, indicating a water content of about 2.6 molecules per unit cell (corresponding to 1.5 wt%).…”
Section: 5-hexadiene In Hs-mor: Experimental Structural Aspectsmentioning
confidence: 99%